Green Marketing and The SDGs: Emerging Market Perspective. - Doe, Joshua; Amoako, George Kofi; Dzogbenuku, Robert Kwame; Adjaison, Geoffrey Kwasi (Emerald, 2020)
The purpose of this paper is to investigate how consumers in emerging market respond to sustainable development goals initiatives by marketers and firms. The study seeks to identify how sustainable marketing strategies contribute to attaining the SDGs in Ghana, a developing and emerging country in sub-Saharan Africa. A positivist methodological framework was used for the collection of data, analysis and theoretical development in this research. A total of 780 questionnaires were handed out. Out of this number, a total of 650 were returned. However, due to missing values,622 valid responses were used for analysis. Of the valid responses, 306 (about 49.23%) were males while 316 were females, representing about 50.8%. Structural equation modelling was used to analyse data and investigate the relationship amongst advertising, packaging, pricing, green marketing strategies and purchasing behaviour. Study findings provide insight into how marketing strategies affect consumer purchasing decisions and brand loyalty. Findings revealed positive relationship between green marketing and purchase behaviour. Empirical results from this study also confirm the mediating role of price on the relationship between green marketing strategies and purchase behaviour. While this study is limited to a single country Ghana, the findings can have far-reaching implications for many countries in the emerging markets sector. The study provides a vivid illustration of how environmental concerns can affect consumers’ attitude towards products or services. Policy on environmental issues can be developed from this study. Marketers can be more effective at how to effect consumer behaviour using findings from this research. Firms employing green marketing strategies must be aware of the importance the youth places on sustainability and develop strategies that enhance social acceptance by the youth. To the authors’ knowledge, sustainable and environmental issues have been researched on, but pricing and advertising have not been used as a mediating variable on purchasing behaviour in Ghana. Moreover, investigation of green marketing strategies and purchase behaviour, advertising packaging and brand loyalty using structural equation modelling analysis within the Ghanaian public space is unique.
Research Paper
Keywords: Ghana; Packaging; Advertising; Purchasing behaviour